Collegial surface acting emotional labour, burnout and intention to leave in novice and pre‐retirement nurses in the United Kingdom: A cross‐sectional study. Issue 1 (15th October 2020) - Theodosius, Catherine; Koulouglioti, Christina; Kersten, Paula; Rosten, Claire
Abstract: Aim: To investigate the relationship between surface and deep acting in nurses' patient‐focused and collegial emotional labour, with emotional exhaustion, depersonalization and personal accomplishment and intention to leave. Design: A cross‐sectional descriptive study using the Emotional Labour Scale, the Maslach Burnout Inventory and intention to leave Yes/No questions with 118 Registered Nurses to measure patient‐focused and collegial emotional labour, burnout and intention to leave. Results: Surface acting in patient‐focused and collegial emotional labour was found to have positive associations with burnout and intention to leave their current job. Only surface acting in patient‐focused emotional labour was positively associated with intention to leave the organization and/or the profession. The novice nurses carried out more deep acting collegial emotional labour than the pre‐retirement nurses. Conclusions: Collegial emotional labour is significant to nurses' intention to leave their current job but not their intention to leave the organization and/or the profession.